2014
DOI: 10.15517/rbt.v62i0.15979
|View full text |Cite
|
Sign up to set email alerts
|

Patterns at Multi-Spatial Scales on Tropical Island Stream Insect Assemblages (Gorgona Island Natural National Park, Colombia, Tropical Eastern Pacific)

Abstract: Tropical Eastern Pacific island streams (TEPis) differ from other neotropical streams in their rainy climate, mixed sedimentary-volcanic geology and faunal composition. Yet, their relationships between environmental characteristics and stream biota remain unexplored. We analyzed the environmental subject at three spatial scales using a fully nested sampling design (6 streams, 2 reaches within each stream, 2 habitats within each reach, and 4 replicates per habitat) on Gorgona Island (Colombia). Sampling was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, stream island insects are influenced not only by habitat characteristics, but they are also associated with spatial processes related to isolation, common to the fauna from insular areas (Thorp & Covich, 2010). Nevertheless, the knowledge on the ecology of stream insects from tropical and oceanic islands is far more developed than in temperate and continental ones (New, 2008;Thorp & Covich, 2010;Ramírez et al, 2012;Longo & Blanco, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, stream island insects are influenced not only by habitat characteristics, but they are also associated with spatial processes related to isolation, common to the fauna from insular areas (Thorp & Covich, 2010). Nevertheless, the knowledge on the ecology of stream insects from tropical and oceanic islands is far more developed than in temperate and continental ones (New, 2008;Thorp & Covich, 2010;Ramírez et al, 2012;Longo & Blanco, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2014, Longo and Blanco 2014, Miyazono and Taylor 2013. Fish assemblages typically become more diverse as stream size increases and assemblage composition often changes by addition of species to the upstream pool (Sheldon 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Many comparisons of species assemblages and habitat conditions have been made between streams, but few studies have reported intra-stream reach assemblage differences (Hughes et al 2006, Gido and Jackson 2010, Espirito-Santo et al 2013, Kanno et al 2014, Longo and Blanco 2014, Longo and Blanco 2014, Miyazono and Taylor 2015. A few of these have noted greater habitat condition variability between streams than within stream reaches.…”
Section: Introductionmentioning
confidence: 99%